(untitled) (Analysis in Theory and Applications, 2013)
Let w be a Muckenhoupt weight and H^p_w(R^n) be the weighted Hardy space. In this paper, by using the atomic decomposition of H^p_w(R^n), we will show that the Bochner-Riesz operators T^δ_R are bounded from H^p_w(R^n) to the weighted weak Hardy spaces WH^p_w(R^n) for 0 < p < 1 and δ=n/p-(n+1)/2. This result is new even in the unweighted case.